Evaluation of dynamic characteristics of the footbridge with integral abutments = Ocena parametrów dynamicznych zespolonej kładki dla pieszych z przyczółkami zintegrowanymi - Pańtak, Marek; Jarek, Bogusław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents the results of dynamic field tests and numerical analysis of the footbridge designed as a three-span composite structure with integral abutments. The adopted design solution which has allowed to achieve a high resistance of the structure to dynamic loads and to meet the requirements of the criteria of comfort of use with a large reserve has been characterized.
Keywords: dynamics; vibrations; footbridges; integral abutments bridges; comfort of use; drgania; kładki dla pieszych; mosty zintegrowane; komfort użytkowania